Improvement of Oxygenation in Severe Acute Respiratory Distress Syndrome With High-Volume Continuous Veno-venous Hemofiltration - Wenmin Yang MD; Jie Hong MD; Qiyi Zeng PhD; Jianping Tao MD; Feiyan Chen MD; Run Dang MD; Yufeng Liang MD; Zhiyuan Wu PhD; Yiyu Yang MD (SAGE Publishing, 2016)
The efficacy and therapeutic mechanisms of continuous renal replacement therapy (CRRT) for improvement of oxygenation in acute respiratory distress syndrome (ARDS) remain controversial. These questions were addressed by retrospective analysis of severe ARDS patients admitted to the pediatric intensive care unit of our hospital from 2009 to 2015 who received high-volume continuous veno-venous hemofiltration during mechanical ventilation. There was a significant improvement in partial oxygen pressure/fraction of inspired oxygen (PaO 2 /FiO 2 ) 24 hours after CRRT onset compared with baseline (median change = 51.5; range = −19 to 450.5; P < .001) as well as decreases in FiO 2 , peak inspiratory pressure, positive end-expiratory pressure, and mean airway pressure ( P < .05). The majority of patients had a negative fluid balance after 24 hours of CRRT. White blood cell (WBC) count decreased in the subgroup with high baseline WBC count ( P < .05). PaO 2 /FiO 2 was higher in ARDS patients with extrapulmonary etiology than in those with pulmonary etiology ( P < .05). Improvement in oxygenation is likely related to both restoration of fluid balance and clearance of inflammatory mediators.